O trabalho docente articulado numa perspectiva colaborativa entre os professores da sala de aula regular e do atendimento educacional especializado - Scaramussa, Patrícia Vassoler (2021)
This research addresses the theme articulated teaching work under the collaborative perspective between the Specialized Education Assistance teachers and those of the Ordinary Classroom. This qualitative analysis is grounded on the ethnographic-type case study. Instruments used in data production were documental analysis, participant observation, semi-structured interview, and focus-groups, permitting us to understand the reality experienced. The research field was the municipal education system of São Gabriel da Palha / ES, involving eight Specialized Educational Assistance teachers and one pedagogue who coordinates special education in the Municipal Education Board; we selected two schools in the municipal education system, including two principals, three pedagogues and eight ordinary-classroom teachers - who had in their classrooms students target audience of special education enrolled. Analysis and dialogues were grounded on Lev Semyonovitch Vygotsky's theoretical contributions emphasizing the importance of social interaction in collective experiences as a form of transforming the other, the environment and oneself. Along the discussion and reflection, the teachers and the other professionals referred the importance of the articulated teaching work and the collaborative actions in ordinary schools in the apprenticeship and development of the special education target-public student. Outcomes have demonstrated that the articulated work under the collaborative perspective still causes discomfort in some teachers from the assessed universe, showing hindrances to partnership movements, mainly due to the necessity of a stronger interaction between professionals, continuous formation, and construction of public policies. It has also been realized that, even though the teachers had been developing the articulated teaching work, actions are not always collaborative, remaining traditional, individualized practices. However, the municipality signals actions multiplication and actions restructuration through collective planning. We conclude that the articulated teaching work under the collaborative perspective potentiates pedagogical actions to supply the singularities of the special education target-public students. As an educational product, we have constructed a reflection proposal on pedagogical actions concerning the town‘s needs, based on observations, analyses, and official documents. That way, the result will help in interventions, with clarification of doubts and challenges observed along the construction of this research.